NTNG2 Mutation: A candidate gene for a new brain-skin disorder with early neuropsychiatric manifestation? An analysis based on 3000 patients - Yuluğ, Burak; Ayaz, Akif (Alanya Alaaddin Keykubat University, 2022)
Aim: In this study, the relationship between genetic analysis and exome sequencing and clinical and neuroimaging findings of four patients from the same family was investigated by analyzing a clinical and genetic (WES) database containing more than 3000 patients. Methods: We analyzed the WES data of approximately 3000 patients performed in our center in terms of NTNG2 biallelic mutations. In addition, MR imaging findings were investigated. Results: We found four patients with the same mutation in the NTNG2 gene, presenting with similar clinical and neuroimaging findings. As a result of filtering, the c242G>A variant was determined in the NTNG2 gene. In addition, mild to severe brain parenchymal volume loss and frontal and temporal lobe atrophy were seen in cases 1, 2, and 4 on axial T2-weighted MRI. c. Conclusion: The current study has similar phenotypic and genotypic features and is a very rare report showing NTNG2 mutation in this context. Existing clinical data are important in choosing NTNG2 gene-related neuropsychiatric disorders as a future treatment target.

Amaç: Bu çalışmada 3000'den fazla hastayı içeren klinik ve genetik (WES) veri tabanını analiz ederek aynı aileden dört hastanın genetik analizi ve ekzom dizilimi ile klinik ve nörogörüntüleme bulguları arasındaki ilişki araştırılmıştır. Yöntem: Merkezimizde 3000 hastanın WES verileri NTNG2 bialelik mutasyonları açısından incelendi. Ayrıca MR görüntüleme bulguları araştırıldı. Bulgular: NTNG2 geninde aynı mutasyona sahip, benzer klinik ve nörogörüntüleme bulguları ile başvuran dört hasta bulundu. Filtreleme sonucunda NTNG2 geninde c.242G>A varyantı belirlendi. Ayrıca aksiyel T2 ağırlıklı MRG'de vaka 1, 2 ve 4'te hafif ila şiddetli beyin parankimal hacim kaybı ve frontal ve temporal lob atrofisi görüldü. Sonuç: Mevcut çalışma benzer fenotipik ve genotipik özelliklere sahip olup bu bağlamda NTNG2 mutasyonunu gösteren çok nadir bir rapordur. Mevcut klinik data NTNG2 geniyle ilişkili nöropsikiyatrik bozukluklarda gelecekteki bir tedavi hedefi olarak seçilmesinde öneme sahiptir.
NTNG2 Mutasyonu: Erken nöropsikiyatrik manifestasyonlu yeni bir beyin-cilt hastalığı için aday bir gen mi? 3000 hasta üzerinden bir analiz
Keywords: Netrin-G2; Synapse Formation; Phenotype; WES Analysis; Schizophrenia; Neuropsychiatric Disease; Netrin-G2; Sinaps Oluşumu; Fenotip; WES Analizi; Şizofreni; Nöropsikiyatrik Hastalık